Cash flow management of commercial grain farmers in the highveld of Mpumalanga - Ngakantsi, Gaopalelwe Mosimanegape (University of the Free State, 2022)
The primary objective of the study is to evaluate the cash flow management of commercial grain farmers in the Highveld region of Mpumalanga. To investigate whether these farmers follow active cash flow management techniques in managing their farming businesses. Additionally, the study aims to investigate the impact of cash flow management on the financial performance reported in the farmers’ annual financial statements. An overview of an understanding of cash flow management and its usefulness are addressed in the literature review, which are supported by a discussion around the use of cash flow budgets in farming businesses. Farm management is also a key aspect of this study because each farm is unique with its set of goals and targets that farmers seek to achieve at the end of the season. Therefore, the functions of farm management are discussed with a focus on planning, execution, control and fine-tuning because these aspects have an impact on the business’s cash flow. Next, the study moves to the research methodology in Chapter 3. The study research methodology used the qualitative research design because interpretivism was the approach used to acknowledge the different realities and truths of the different farmers that participated in the study. The information was collected through semi-structured interviews with the participants to understand each participant’s viewpoint. The interview schedule was compiled and used to gather the data. The research findings from the interviews identified 10 themes that resonated with the participants. These themes were discussed and assessed, leading to the identification of 4 gaps that exist. The 10 themes were able to address the three secondary objectives of the study and the 4 gaps were complemented by 4 recommendations for the study. The conclusions derived were firstly, farmers have the knowledge and understanding of cash flow management and its potential impact on a farming business. However, farmers do not practically put this knowledge to use in their farming businesses. Secondly, good cash flow management alone could not conclusively be linked to the profit or loss reported on the farmers’ annual financial statements. The aim and objectives of the study were achieved. The study limitations were that it was confined to the Highveld region of Mpumalanga, and limited to grain commercial farmers currently banked with First National Bank. Additionally, a random sample of farmers was selected on the basis that each participant was not to plant more than 3000 hectares per season.
Dissertation (MBA (Business Administration))--University of the Free State, 2022